Mitral stenosis obscuring the diagnosis of plexogenic pulmonary arteriopathy and familial pulmonary hypertension. Issue 3 (1st March 2000) - Langleben, David; Lamoureux, Esther; Marcotte, Francois; Schlesinger, Robert; Dragatakis, Leonidas; Crowe, Marie Josee; Langlois, Yves; Lemire, Francois; White, Michel
Abstract : A patient who died after surgery for critical mitral stenosis was found to have underlying unrecognised plexogenic pulmonary arteriopathy and familial pulmonary hypertension. The importance of recognising familial pulmonary hypertension is discussed, together with the contribution of genetic and other risk factors to plexogenic pulmonary arteriopathy.